Influence of Tire-Recycled Steel Fibers on Strength and Flexural Behavior of Reinforced Concrete. (20th April 2020) - Zhang, Yancong; Gao, Lingling
Abstract : Tire production is increasing every year due to the increase in vehicle sales. The generation and disposal of waste are inherent to life itself and have presented very serious problems to the human community in China. Recently, some research has been devoted to the use of tire-recycled steel fibers in concrete. This study is focusing on the use of tire-recycled steel fibers. Several volume ratios of tire-recycled steel fibers were used in concrete mix to fabricate and test. Reinforced concrete obtains evidence and satisfactory improvement by adding tire-recycled steel fibers, mostly in compressive strength, splitting strength, flexural tensile strength, and flexural toughness. The strength and flexural toughness of the tire-recycled steel fiber reinforced concrete are lower than those of industrial steel fibers. To obtain concrete with approximately the same strength or toughness, the content of tire-recycled steel fibers should be about 1%-2% higher than that of industrial steel fibers. In addition, the load-deflection curve tends to become fuller after the first crack, and the second peak of the load continues to increase. The steel fiber reinforced concrete is getting closer to the ideal elastic-plastic material.